Rural youth and the future of entrepreneurship: Insights from Jambi Province's millennials - Hardiani, Hardiani; Amril, Amril (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
This study aims to examine the entrepreneurial intentions and characteristics of the millennial generation in rural areas of Jambi Province and to identify the factors influencing these intentions. Data were collected through a survey of millennials in rural Jambi and were analyzed using descriptive statistical tools and the Structural Equation Modeling Partial Least Square (SEM-PLS) approach. The key variables evaluated were individual characteristics, attitudinal factors, and contextual factors. The findings indicate that the entrepreneurial interest of millennials in rural Jambi is relatively high, signaling a promising potential for the emergence of young entrepreneurs in the future. The surveyed millennials' attitudinal and contextual factors directly influence this entrepreneurial interest. While individual characteristics do not directly impact entrepreneurial intentions, they exert an indirect influence mediated by attitudinal and contextual factors.